Analisis Keterlambatan Pemberitahuan Pengambilalihan Saham Ditinjau dari Hukum Persaingan Usaha Tidak Sehat (Studi Kasus Putusan Nomor 17/KPPU-M/2020) - Salsabilla Hassani; Suherman Suherman (Jurnal Selat, 2022)
Based on article 29 of Law Nomor 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, it is explained that the acquisition of shares that have an asset value and or sales value exceeding a certain amount as regulated in Article 5 of Government Regulation Nomor 57 of 2010 is required to carry out a notification to KPPU no later than 30 working days after it is legally effective. However, it was found that through the KPPU decision Nomor17/KPPU-M/2020, it was stated that PT Saratoga Investama Sedaya has been proven to have violated Article 29 of Law Nomor 5 of 1999 in conjunction with Article 5 PP Nomor 57 of 2010. This study aims to find out how to prove the elements of a violation of late notification of share takeover by PT Saratoga Investama Sedaya. This research method is a normative juridical method. The results of this research are that the Commission Council stated that the takeover of shares by the Reported Party did not have the potential to cause monopolistic practices and/or unfair business competition. Because there is no change in market power and there is no vertical integration. However, the Reported party had to bear a fine of Rp. 1 billion because it was stated that he had violated Article 29 of Law Nomor 5 of 1999 in conjunction with Article 5 of PP Nomor 57 of 2010.